ACCURACY AND READABILITY ON THE TRANSLATIONS OF ONOMATOPOEIA IN THE MAZE RUNNER NOVEL INTO INDONESIA LANGUAGE - Anindya, Widya Dara; Sutrisno, Adi (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
This article discusses about the accuracy and readability on the translations of onomatopoeia in The Maze Runner novel translated by Yunita Candra in order to evaluate the translation quality. All onomatopoeia both from English or translated novel were collected and then looked for the meaning in Cambridge Dictionary, Oxford Dictionary, Indonesian Dictionary ( KBBI), and in some sources such as books, internet, or cross checking from native or experts, then compared and determined the accuracy and readability level using Translation Accuracy Assessment Instrument and Translation Readability Assessment Instrument [1]. The result showed that accuracy and readability related to each other. Onomatopoeia translated accurately tended to have low readability level and there were onomatopoeia intentionally translated inaccurately to obtain high readability level. Nevertheless, there were also the translations of onomatopoeia with high accuracy level and readability level.